Senegal Investment Climate Reform Action Plan - World Bank (World Bank, Washington, DC, 2021)
This Investment Climate Reform Action Plan summarizes the economic context of Senegal as well as the main constraints private sector faces in the country, and provides a number of recommendations on which the World Bank (WB) and the Government of Senegal (GOS) can collaborate on to eliminate poverty and promote shared prosperity. Section one leverages an Investment Climate Scan drawing on economic data from global resources summarizes the situation of Senegal with reference to the macroeconomic and political factors that are impeding its development. The analysis includes benchmarking different IC characteristics against selected structural, aspirational, and regional comparators. Annex one expands on the Scan’s methodology. Section two summarized relevant WBG diagnostics by presenting a stocktaking of available diagnostics and efforts to improve the country’s investment climate. Section three distils the constraints Senegal faces in improving its investment climate, with a special focus on the additional challenges faced by the country during the COVID-19 crisis. Section four outlines WB recommendations through the Reform Action Plan and charts a path toward future partnership with the GOS in achieving these objectives.